Solidaridad, dolor y resistencia: el mural de Sofía Bassi y sus colegas rupturistas tras las rejas (REVISTA NODO, 2026)
The text analyzes the mural created in the Acapulco prison by the Surrealist painter Sofía Bassi, with the supportive collaboration of her colleagues from La Ruptura movement: Alberto Gironella, José Luis Cuevas, Rafael Coronel, and Francisco Corzas. The paper begins with a summary of the life of the artist and of her tragic fate following the murder of her son-in-law, for which she took responsibility, always claiming it was an accident. It then offers a detailed iconographic analysis of each of the mural's sections, paying particular attention to their individual and shared themes, the use of intertextual artistic references, and the inclusion of portraits and self-portraits, especially of Bassi herself and her daughter Claire. Special attention is given to the section entitled La Calumnia, created by Bassi, contextualizing the work with the artist´s pictorial and philosophical sources, and above all highlighting her extraordinary defense of her daughter throughout the process. Finally, the text reflects on art as a means of overcoming pain, protesting, and social resistance, as well as on the importance of the collective mural in the history of Mexican art, both for its powerful denunciation of the abuses of power and the fragility of justice in 1960s Mexico, and for its defense of human rights in general, and of women's rights in particular.